TINJAUAN GAME PUZZLE VICTORIAN MYSTERIES: WOMAN IN WHITE MENGGUNAKAN PENDEKATAN SEMIOTIKA - WIEKE TASMAN; ELIZABETH WIANTO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2018)
Game already became common media in any society. It’s ideas could be from anywhere. This example is proven in game titled Woman in White. Adapted from Wilkie Collin’s sensational novel. Mr Collin’s novel in similar title was very popular then, though after one hundred and fifty years already adapted dan raised into newer meaning. This new meaning of ‘Woman in White’ makes the game became new media design and still entertains its audiens. This study, try to analize similar aspect in novel that used in this game as formal or non-formal assets, using visual semiotics. Precisely using classic theory from Saussure, Peirce and Barthes. The results of the analysis aim to show that a game designed based on novel inspiration or a popular story needs to remain true to the story even though this media does not have a full story telling. Keywords: game; puzzle; semiotics; urban legends